Public Perception of Complete Systematic Land Registration (PTSL) Services at the Madiun City Land Office - Sunariyanto, Dhuhri; Mahasari, Jamaluddin; Ibrahim; Wahyudi, Heri (GoAcademica Research & Publishing, 2024)
The study investigates the community's response to PTSL (One Stop Integrated Land Service) at the Madiun City Land Office, with the assistance of stakeholders, serving as a reflective tool for enhancing the quality of land services. Discrepancies in previous research findings regarding public perceptions of public service quality highlight the necessity for further exploration. Focused on understanding the perceptions of PTSL participants in Madiun City, particularly as 2021 marks the final year of PTSL implementation in the area, the research employs a mixed-methods approach. Findings reveal a prevailing lack of public awareness regarding the PTSL service process in Madiun City, alongside inaccurate assumptions regarding the services provided by the Land Office. Consequently, efforts to disseminate accurate information to the public are deemed imperative.